The effects of high intensity interval training on pulmonary function - Dunham, Cali A. (Kansas State University, 2010)
High-intensity interval training (HIT) has been utilized as a time-efficient strategy to induce numerous physiological adaptations and improve performance usually associated with “traditional” endurance training (ET). It is not known however, if HIT might lead to improvements in pulmonary function. Therefore we hypothesized that HIT would increase respiratory muscle strength and expiratory flow rates. Fifteen healthy subjects were randomly assigned to an ET group (n = 7) and a HIT group (n = 8). All subjects performed an incremental test to exhaustion (VO2 max) on a cycle ergometer prior to and after training. Standard pulmonary function tests, maximum inspiratory pressure (PImax), maximum expiratory pressure (PEmax), and maximal flow volume loops, were performed pre training and after each week of training. HIT subjects performed a four week training program on a cycle ergometer at 90% of their VO2 max final workload while the ET subjects performed exercise at 60-70% of their VO2 max final workload. All subjects trained three days/ week. The HIT group performed five one-minute bouts with three minute recovery periods and the ET group cycled for 45 minutes continuously at a constant workload. A five-mile time trial was performed prior to training, after two weeks of training, and after four weeks of training. Both groups showed similar (p<0.05) increases in VO2 max (~8-10%) and improvements in time trials following training (HIT 6.5 ± 1.3%, ET 4.4 ± 1.8%) with no difference (p>0.05) between groups. Both groups increased (p<0.05) PImax post training (ET ~25%, HIT ~43%) with values significantly higher for HIT than ET. There was no change (p>0.05) in expiratory flow rates with training in either group. These data suggest that whole body exercise training is effective in increasing inspiratory muscle strength with HIT leading to greater improvements than ET. Also, HIT offers a time-efficient alternative to ET in improving aerobic capacity and performance.
Keywords: pulmonary function; high intensity interval training; Health Sciences, General (0566)